A mixed methods comparison of gang and race motivated violent incident involvement in a youth correctional setting. Issue 3 (3rd July 2018) - Scott, Daniel
ABSTRACT: Scholarship has examined both gang and race violence in a variety of settings. However, there has been little research addressing the characteristics of gang and race related violence within youth correctional facilities. This article fills this research gap by utilizing 404 violent incident narratives provided by incarcerated male youth. Mixed methods analyses are conducted on gang and race motivated violence at the situational level. Multivariate analyses reveal significant differences in violent incidents when comparing number of racial groups involved and participant dynamic. Qualitative analyses compare themes related to the subculture of violence and correctional setting across the different contexts in which gang and race motivated violence occurs. The results have implications for theory, policy, and programs within youth correctional facilities.